Endogenous and Exogenous KdpF Peptide Increases Susceptibility of Mycobacterium bovis BCG to Nitrosative Stress and Reduces Intramacrophage Replication - Rosas Olvera, Mariana; Vivès, Eric; Molle, Virginie; Blanc-Potard, Anne-Béatrice; Gannoun-Zaki, Laila (Frontiers in Cellular and Infection Microbiology, 2017)
Emerging antibiotic resistance in pathogenic bacteria like Mycobacterium sp., poses a threat to human health and therefore calls for the development of novel antibacterial strategies. We have recently discovered that bacterial membrane peptides, such as KdpF, possess anti-virulence properties when overproduced in pathogenic bacterial species. Overproduction of the KdpF peptide in Mycobacterium bovis BCG decreased bacterial replication within macrophages, without presenting antibacterial activity. We propose that KdpF functions as a regulatory molecule and interferes with bacterial virulence, potentially through interaction with the PDIM transporter MmpL7. We demonstrate here that KdpF overproduction in Mycobacterium bovis BCG, increased bacterial susceptibility to nitrosative stress and thereby was responsible for lower replication rate within macrophages. Moreover, in a bacterial two-hybrid system, KdpF was able to interact not only with MmpL7 but also with two membrane proteins involved in nitrosative stress detoxification (NarI and NarK2), and a membrane protein of unknown function that is highly induced upon nitrosative stress (Rv2617c). Interestingly, we showed that the exogenous addition of KdpF synthetic peptide could affect the stability of proteins that interact with this peptide. Finally, the exogenous KdpF peptide presented similar biological effects as the endogenously expressed peptide including nitrosative stress susceptibility and reduced intramacrophage replication rate for M. bovis BCG. Taken together, our results establish a link between high levels of KdpF and nitrosative stress susceptibility to further highlight KdpF as a potent molecule with anti-virulence properties.